Insulin resistance and adipokine levels correlate with early atherosclerosis – a study in prediabetic patients - Mihai Bogdan Mircea (Open Medicine, 2014)
Cardiovascular risk of prediabetes is still subject to controversies. We analyzed the associations between insulin resistance, adipokines and incipient atherosclerosis estimated by intima-media thickness (IMT) in a cross-sectional study on 122 prediabetic subjects without clinical signs of atherosclerotic disease. Homeostasis model assessment of insulin resistance (HOMA-IR, calculated as fasting insulin × fasting plasma glucose / 22.5), adiponectin, leptin, leptin-to-adiponectin ratio, carotid and femoral IMT were evaluated. We also assessed other parameters related to insulin resistance and adipokines (HbA1c, anthropometric and lipid parameters), as they may also influence atherosclerosis. Carotid IMT was correlated to adiponectin and leptin-to-adiponectin ratio (all p < 0.05), but not with HOMA-IR or leptin, while femoral IMT showed no relationship with these factors. After adjusting for leptin, leptin-to-adiponectin ratio, triglycerides, HDL-cholesterol, cholesterol-to-HDL ratio, triglycerides-to-HDL ratio and HbA1c, IMT values became correlated with HOMA-IR. Adjustment for HOMA-IR induced the appearance of new correlations between adipokines and both IMT values. In conclusion, insulin resistance and adipokines seem related to IMT in prediabetic subjects without clinical signs of arterial obstruction.